Kinetic analysis of aptazyme-regulated gene expression in a cell-free translation system: Modeling of ligand-dependent and -independent expression - Kobori, Shungo (Cold Spring Harbor Laboratory Press, 2012)
Aptazymes are useful as RNA-based switches of gene expression responsive to several types of compounds. One of the most important properties of the switching ability is the signal/noise (S/N) ratio, i.e., the ratio of gene expression in the presence of ligand to that in the absence of ligand. The present study was performed to gain a quantitative understanding of how the aptazyme S/N ratio is determined by factors involved in gene expression, such as transcription, RNA self-cleavage, RNA degradation, protein translation, and their ligand dependencies. We performed switching of gene expression using two on-switch aptazymes with different properties in a cell-free translation system, and constructed a kinetic model that quantitatively describes the dynamics of RNA and protein species involved in switching. Both theoretical and experimental analyses consistently demonstrated that factors determining both the absolute value and the dynamics of the S/N ratio are highly dependent on the routes of translation in the absence of ligand: translation from the ligand-independently cleaved RNA or leaky translation from the noncleaved RNA. The model obtained here is useful to assess the factors that restrict the S/N ratio and to improve aptazymes more efficiently.